Membangun Kredibiltas Kekristenan Dalam Menghadapi Ajaran Sesat Berdasarkan 1 Yohanes 4:1-6 - Fernando Tambunan; Heri Victor Ambarita (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Since the beginning of the first century until now there have been many teachings that deviate from the Bible. Unhealthy teaching can undermine the faith and trust of Christians. This can happen if God's congregation is not properly equipped and taught the truth of God's Word. This study aims at how Christians build the credibility of Christianity in the face of heresies. The method used in this research is descriptive method. In this study it was found that in 1 John 4:1-6, the apostle John provides a solution in building the credibility of believers when facing heresies. First: test the spirit; second: knowing the Spirit of God, and third: knowing the status of a child of God.